Socio-economic Relations in Ptolemaic Pathyris : A Network Analytical Approach to a Bilingual Community. Volume 2. - Tambs, Lena (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2022., 2022)
This study tackles pertinent questions about daily life and socio-economic interactions in the late Ptolemaic town of Pathyris (186-88 BCE) through an empirically grounded network analysis of 428 Greek and Demotic documents associated with 21 archives from the site. The author moves beyond traditional boundaries of Egyptological and Papyrological research by means of an innovative and interdisciplinary methodology - zigzagging back and forth between archaeological field survey, close reading of ancient texts, formal methods of Social Network Analysis (SNA) and explanatory theories and concepts borrowed from economics and other social sciences. This is volume 2 of a two-volume set.